Activity of Sulfa Drugs and Their Combinations against Stationary Phase B. burgdorferi In Vitro - Jie Feng; Shuo Zhang; Wanliang Shi; Ying Zhang (MDPI AG, 2017)
Lyme disease is a most common vector-borne disease in the US. Although the majority of Lyme patients can be cured with the standard two- to four-week antibiotic treatment, at least 10%-20% of patients continue to suffer from prolonged post-treatment Lyme disease syndrome (PTLDS). While the cause for this is unclear, one possibility is that persisting organisms are not killed by current Lyme antibiotics. In our previous studies, we screened an FDA drug library and an NCI compound library on B. burgdorferi and found some drug hits including sulfa drugs as having good activity against B. burgdorferi stationary phase cells. In this study, we evaluated the relative activity of three commonly used sulfa drugs, sulfamethoxazole (Smx), dapsone (Dps), sulfachlorpyridazine (Scp), and also trimethoprim (Tmp), and assessed their combinations with the commonly prescribed Lyme antibiotics for activities against B. burgdorferi stationary phase cells. Using the same molarity concentration, dapsone, sulfachlorpyridazine and trimethoprim showed very similar activity against stationary phase B. burgdorferi enriched in persisters; however, sulfamethoxazole was the least active drug among the three sulfa drugs tested. Interestingly, contrary to other bacterial systems, Tmp did not show synergy in drug combinations with the three sulfa drugs at their clinically relevant serum concentrations against B. burgdorferi. We found that sulfa drugs combined with other antibiotics were more active than their respective single drugs and that four-drug combinations were more active than three-drug combinations. Four-drug combinations dapsone + minocycline + cefuroxime + azithromycin and dapsone + minocycline + cefuroxime + rifampin showed the best activity against stationary phase B. burgdorferi in these sulfa drug combinations. However, these four-sulfa-drug-containing combinations still had considerably less activity against B. burgdorferi stationary phase cells than the Daptomycin + cefuroxime + doxycycline used as a positive control which completely eradicated B. burgdorferi stationary phase cells. Future studies are needed to evaluate and optimize the sulfa drug combinations in vitro and also in animal models.